Method for testing internal permeability of fiber preform by using carbon nanotube film as sensor
By using carbon nanotube membrane sensor to measure the resistance changes and position inside the fiber preform and computed with Darcy's law to calculate the unsaturated permeability, the problem of difficulty in accurately testing the internal permeability of fiber preforms in the prior art is solved, and the problem of the difficulty in accurately testing the internal permeability of fiber preforms is realized. Highly accurate testing method.
Patent Information
- Application Number
- CN202411138871.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to accurately test the unsaturated permeability inside the fiber preform, and implanting the sensor will interfere with the flow of resin, resulting in unreliable results.
The carbon nanotube membrane is used as a sensor to measure its resistance changes and position, and the unsaturated permeability inside the fiber preform is calculated based on Darcy's law.
Simple and accurate testing of the internal unsaturated permeability of the fiber preform is achieved, and the applicability and accuracy of the test are improved.
Smart Images

Figure CN119223832A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber reinforcement process characteristic testing, in particular to a fiber preform internal permeability testing method using a carbon nanotube film as a sensor. Background Art
[0002] Liquid molding process is a composite molding process that drives the resin to flow and penetrate under injection pressure or vacuum negative pressure to achieve the impregnation of fiber-reinforced materials in a closed mold cavity. It has the advantages of low cost, high production efficiency, low production pollution, stable product quality, and excellent performance. When using liquid molding process to prepare composite products, its process quality is affected by many factors, such as injection port, overflow port, process parameters, etc. If the above factors are not designed properly, it will usually lead to defects such as dry spots and voids, which seriously affect the product quality. Permeability is a key process characteristic of fiber preforms and has an important influence on the infiltration speed and direction of resin. At present, the more widely used test method is to use Darcy's law to quantitatively describe the process of resin fluid flowing in the porous medium formed by fiber preforms. Permeability is determined by fiber size and reinforcement structure. It is an important basis for liquid molding mold design and process parameter formulation. Accurately obtaining the permeability of fiber preforms is crucial to shortening product manufacturing cycle and ensuring product quality.
[0003] At present, as the key data of liquid molding process simulation, the test method of fiber preform surface permeability is relatively mature. It adopts unidirectional flow or radial flow, records the relationship between flow front and time through visual operation or introduction of monitoring system, and calculates surface permeability using Darcy's law. However, due to the different fiber volume fractions and fiber network structures, there are often obvious differences between surface permeability and internal permeability, and it is difficult to visualize the resin flow inside the fiber preform. In addition, the implantation of sensors inside the preform often interferes with the flow of resin, making the result of recording the relationship between flow front and time unreliable. Therefore, this field urgently needs to develop a relatively simple, accurate, and applicable test method that can obtain the unsaturated permeability inside the fiber preform. Summary of the invention
[0004] To solve the above problems, the present invention proposes a method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, which can accurately test the unsaturated permeability inside the fiber preform in a relatively simple manner.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] A method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, comprising:
[0007] Prepare a permeability test system; the permeability test system includes a test mold, a carbon nanotube film sensor and a data collection device;
[0008] Put the carbon nanotube film sensor into the fiber preform to be tested with the preformed hole, put it in the preset position in the test mold, and assemble the test mold;
[0009] connecting the carbon nanotube film sensor in the test mold to the data collection device;
[0010] Infusing the test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculating the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform;
[0011] Draw a flow front position square-time curve inside the fiber preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform;
[0012] The slope of the flow front position square-time curve inside the fiber preform is substituted into Darcy's law to calculate the unsaturated permeability inside the fiber preform.
[0013] Optionally, the preparation of the permeability test system specifically includes:
[0014] Prepare a test mold; the test mold includes an upper cover plate, a gasket, and a lower base plate; the upper cover plate is provided with injection / discharge ports at the center of the left and right sides, through holes are provided around it, and the center part of the upper cover plate is a glass observation window; the gasket has a thickness ranging from 10 to 50 mm, the middle part is hollowed out, and through holes are present around it in the same structure as the upper cover plate; the lower base plate is a rectangular structure, and the edges have through holes in the same structure as the upper cover plate.
[0015] The permeability test system is prepared, and the preparation of the carbon nanotube film sensor is also included:
[0016] A carbon nanotube film sample of preset specifications was cut out using a laser marking machine, and copper wire was used to connect the two ends of the carbon nanotube film sample. To ensure the conductivity of the copper wire and the carbon nanotube film, the two ends of the copper wire were polished with sandpaper before connection. One end of the copper wire was bonded to the carbon nanotube film using conductive silver glue, and the other end was reserved. The bonded sensor was cured and placed in a glass fiber sleeve with a loose surface to obtain a prepared carbon nanotube film sensor. The purpose of using a glass fiber sleeve is to increase the sensitivity of the carbon nanotube film's resistance to resin impregnation and improve the accuracy of the flow front test.
[0017] The thickness of the carbon tube film is in the range of 10-15 μm, the initial resistance range is 10-30Ω:.
[0018] The fiber preform includes fiber types including carbon fiber, glass fiber, basalt fiber, aramid fiber, silicon carbide fiber and the like.
[0019] The fiber preform, the preform types include fabric laminates, woven fabrics, braided fabrics, needle-punched preforms, stitched fabrics, etc.
[0020] The glass fiber sleeve has a length ranging from 30 to 50 mm, an inner diameter ranging from 1 to 2 mm, a wall thickness ranging from 0.1 to 0.2 mm, and a linear density ranging from 0.01 to 0.03 g / cm.
[0021] Optionally, the carbon nanotube film sensor is placed in a preformed fiber to be tested with a preformed hole, placed at a preset position in the test mold, and the test mold is assembled, specifically including:
[0022] Prefabricate holes at intervals on the preform to be tested;
[0023] Putting the prepared carbon nanotube film sensor into the hole of the preform to be tested;
[0024] placing a preform of an assembled carbon nanotube film sensor on the lower base plate;
[0025] Place the gasket on the lower base plate. The total thickness of the gasket should be consistent with that of the preform. While reserving the injection / discharge port position, lay a sealing tape with the same thickness as the gasket around the preform to be tested to ensure a vacuum environment.
[0026] The upper cover plate is placed on the lower base plate, and bolts are used to lock and seal the upper cover plate, the gasket, and the lower base plate through the through holes around the upper cover plate, the gasket, and the lower base plate in sequence, and the test mold is assembled.
[0027] The prefabricated holes have a diameter range of 2-4 mm and a spacing range of 5-20 mm.
[0028] Optionally, the step of connecting the carbon nanotube film sensor in the test mold to the data collection device specifically includes:
[0029] The data collection device includes a digital multimeter and a computer;
[0030] The other end of the copper wire of the carbon nanotube film sensor previously reserved is connected to the digital multimeter; the digital multimeter is connected to the computer.
[0031] Optionally, the step of pouring the test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time by the data collection device, and calculating the distances of different carbon nanotube film sensors relative to the injection surface of the fiber preform, specifically includes:
[0032] Infusing the test liquid into the test mold, and recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device;
[0033] According to the position of each carbon nanotube film sensor laid inside the fiber preform, and according to the position of each carbon nanotube film sensor relative to the injection surface of the fiber preform, the distances l1, l2, l3, etc. of each carbon nanotube film sensor relative to the injection surface of the fiber preform are calculated from bottom to top. n .
[0034] Optionally, the step of drawing a flow front position square-time curve inside the fiber preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform specifically includes:
[0035] Draw a resistance-time point line graph according to the change of the resistance of the carbon nanotube film sensor over time;
[0036] Draw a resistance relative change rate percentage-time curve graph according to the resistance-time point line graph;
[0037] The response time s1, s2, s3, ..., of the test liquid to each carbon nanotube film sensor is determined according to the resistance change rate mutation point of the resistance relative change rate percentage-time curve. n ; The mutation point is defined as the percentage of relative resistance change rate of three consecutive points after the mutation point is greater than 0.5%;
[0038] Determine the position and time corresponding to the contact of the test liquid flow front with the carbon nanotube film sensor as follows: L1 = l1, t1 = s1; L2 = l2, t2 = s2; ...; L n = l n , t n =s n ;
[0039] A flow front position square-time curve inside the fiber preform is plotted based on the corresponding relationship between the position L of the test liquid flow front and time t.
[0040] Optionally, substituting the slope of the flow front position square-time curve inside the fiber preform into Darcy's law to calculate the unsaturated permeability inside the fiber preform specifically includes:
[0041] Obtaining the slope λ of the flow front position square-time curve inside the fiber preform by linear fitting;
[0042] The unsaturated permeability inside the fiber preform is calculated according to Darcy's law. Where η is the viscosity of the test liquid; φ is the porosity of the fiber preform; ΔP is the injection pressure.
[0043] A method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, comprising:
[0044] Permeability testing system; the permeability testing system comprises a testing mold, a carbon nanotube film sensor and a data collection device;
[0045] A sensor placement and mold assembly module, used to place the fiber preform to be tested and the carbon nanotube film sensor at a preset position in the test mold according to a preset sequence, and assemble the test mold;
[0046] A data collection device connection module, used to connect the carbon nanotube film sensor in the test mold to the data collection device;
[0047] A data collection and recording module, used for pouring a test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculating the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform;
[0048] A curve drawing module, used for drawing a flow front position square-time curve according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform;
[0049] The permeability calculation module is used to substitute the slope of the flow front position square-time curve inside the fiber preform into Darcy's law to calculate the unsaturated permeability inside the fiber preform.
[0050] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0051] The present invention provides a method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, the method comprising: preparing a permeability testing system; the permeability testing system comprising a testing mold, a carbon nanotube film sensor and a data collection device; laying the fiber preform to be tested and the carbon nanotube film sensor at a preset position in the testing mold in a preset order, and assembling the testing mold; connecting the carbon nanotube film sensor in the testing mold to the data collection device; pouring a testing liquid into the testing mold, recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculating the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform; and drawing a flow front position square-time curve (L) inside the fiber preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform. 2 -t curve); L inside the fiber preform 2 The slope of the -t curve is substituted into Darcy's law to calculate the unsaturated permeability inside the fiber preform. The method of the present invention can obtain the unsaturated permeability inside the fiber preform in a relatively simple and highly applicable manner, and improves the accuracy of testing the unsaturated permeability of the fiber preform. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0053] Figure 1 A flow chart of a permeability testing method for monitoring flow front based on a carbon nanotube membrane sensor of the present invention;
[0054] Figure 2 A schematic diagram of the structure of a test mold provided by an embodiment of the present invention;
[0055] Figure 3 Schematic diagram of a carbon nanotube membrane containing a glass fiber sleeve in an embodiment of the present invention.
[0056] Figure 4 A schematic diagram of the overall assembly of a permeability testing system provided by an embodiment of the present invention;
[0057] Figure 5 A schematic diagram of a resistance relative change rate percentage-time curve provided in Example 1 of the present invention;
[0058] Figure 6L in the embodiment of the present invention 2 —Schematic diagram of the fitting curve of t;
[0059] Explanation of the reference numerals: 1 upper cover plate, 1-1 through hole, 1-2 glass observation window, 1-3 glue inlet / injection port; 2 gasket, 2-1 through hole; 3 lower base plate, 3-1 through hole. DETAILED DESCRIPTION
[0060] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] The purpose of the present invention is to provide a method for testing the internal permeability of a fiber preform using a carbon nanotube membrane as a sensor, which can obtain the unsaturated permeability inside the fiber preform in a relatively simple and applicable manner and improve the accuracy of testing the unsaturated permeability of the fiber preform.
[0062] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0063] Figure 1 This is a flow chart of a method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor according to the present invention. Figure 1 The present invention provides a method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, which specifically includes:
[0064] Step 1: Prepare a permeability test system; the permeability test system includes a test mold, a carbon nanotube film sensor, and a data collection device.
[0065] The present invention discloses a method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, based on a permeability testing system, which includes a carbon nanotube film sensor (also referred to as a carbon nanotube sensor), a testing mold, and a data collection device. The present invention method lays multiple carbon nanotube film sensors in parallel and at intervals inside a fiber preform, monitors the time required for the permeating liquid to reach a specified position through the change in the resistivity thereof, and then obtains the L of the liquid perfused into the fiber preform. 2 -t curve, combined with parameters such as injection pressure, liquid viscosity, and porosity, the unsaturated permeability inside the fiber preform is calculated.
[0066] The step 1 is to prepare a permeability test system, which specifically includes: preparing a test mold, preparing a carbon nanotube film sensor, and preparing a data collection device.
[0067] Figure 2 This is a schematic diagram of the structure of the test mold provided by the embodiment of the present invention. Figure 2 The test mold includes an upper cover plate 1, a gasket 2 and a lower base plate 3. The upper cover plate 1 is provided with a glue injection / discharge port 1-3 at the left and right sides of the center, and is provided with through holes 1-1 around it. The center part of the upper cover plate is a glass observation window 1-2; the gasket 2 has a thickness ranging from 10 to 50 mm, a hollow middle part, and has through holes 2-1 around it in the same structure as the upper cover plate; the lower base plate 3 is a rectangular parallelepiped structure, and has through holes 3-1 at the edge in the same structure as the upper cover plate.
[0068] In step 1, the data collection device is usually composed of a digital multimeter and a computer. When performing the unsaturated permeability test inside the fiber preform, the edge of the carbon nanotube film sensor is connected to a copper wire through conductive silver glue solidification to form a resistance response element, and the other end of the copper wire is connected to a digital multimeter, and the diameter of the copper wire should be less than 0.15 mm.
[0069] In step 1, the process of preparing the carbon nanotube film sensor includes:
[0070] Step 1.1: Cut out carbon nanotube film samples of preset specifications using a laser marking machine;
[0071] In a specific embodiment, a carbon nanotube film sample with a size of 30 mm×2 mm×12 μm (length×width×thickness) can be cut out by a laser marking machine, and the initial resistance range is 10-20Ω.
[0072] Step 1.2: Use sandpaper to polish the insulation layer at both ends of the copper wire;
[0073] In a specific embodiment, the edges of both ends of the copper wire can be polished with 1200-grit sandpaper to cause the insulating protective layer on the edges of the copper wire to fall off.
[0074] Step 1.3: Use conductive silver glue to bond one end of the polished copper wire to the carbon nanotube film sample, and leave the other end for later use, and compact and solidify;
[0075] One end of the copper wire with the insulating layer polished off is fixed on the carbon nanotube film sample with conductive silver glue, and the other end is kept for use. It is covered with polytetrafluoroethylene cloth, placed between two flat plates and compacted, and sent into an oven to cure and form at 100℃ / 2h.
[0076] Step 1.4: placing the solidified carbon nanotube film into a glass fiber sleeve with a loosened surface to make a carbon nanotube film sensor;
[0077] Figure 3 FIG. 1 is a schematic diagram of a carbon nanotube film containing a glass fiber sleeve in an embodiment of the present invention, see Figure 3 , a certain number of cuts are made on the surface of the glass fiber sleeve with a knife, the resin solution is allowed to flow as much as possible without affecting the carbon nanotube film by the carbon fiber signal in the fiber preform, and the solidified carbon nanotube film is placed in the glass fiber sleeve to prepare the carbon nanotube film sensor. In a specific embodiment, the glass fiber sleeve used has a length of 35 mm, an outer diameter of 1 mm, a wall thickness of 0.1 mm, and a linear density of 0.017 g / cm.
[0078] Step 2: Place the carbon nanotube film sensor into the preformed fiber to be tested with the preformed hole, place it at a preset position in the test mold, and assemble the test mold;
[0079] The step 2 is to place the carbon nanotube film sensor into a fiber preform to be tested (which may be a needle-punched fiber preform, a three-dimensional woven preform, a woven preform, etc.) with prefabricated holes, and place it at a preset position in the test mold, and assemble the test mold, which specifically includes:
[0080] Step 2.1: Preform holes at every other end of the preform to be tested;
[0081] In a specific embodiment, a fiber preform having a size of 70×25×15 mm (length×width×thickness) may be preformed with holes having a diameter of 3 mm every 10 mm in the length direction.
[0082] Step 2.2: Place the prepared carbon nanotube film sensor into the hole of the preform to be tested;
[0083] The carbon nanotube film sensor which is sheathed in the glass fiber sleeve after surface loosening treatment is put into the prefabricated hole of the fiber preform to be tested, and is placed in the center of the lower bottom plate.
[0084] Step 2.3: Place the gasket on the lower base plate. The total thickness of the gasket should be consistent with that of the preform. While reserving the injection / discharge port position, lay a sealing tape of the same thickness as the gasket around the preform to be tested to ensure a vacuum environment. Place the upper cover plate on the lower base plate and use bolts to lock it tightly through the through holes around the upper cover plate, gasket, and lower base plate to assemble the test mold.
[0085] Among them, when placing the gasket, the total thickness of the gasket should be consistent with the thickness of the fiber preform. Considering that the carbon nanotube film sensor is placed inside the fiber preform, directly placing a gasket with a thickness consistent with the thickness of the fiber preform will cause the protruding part of the carbon nanotube film sensor from the fiber preform to bend, which may cause the carbon nanotube film sensor to break. A gasket of a certain thickness should be placed first so that the height reaches the laying height of the carbon nanotube film sensor, and sealing tape should be laid along the inside of the gasket. The protruding part of the carbon nanotube film sensor from the fiber preform is fixed on the sealing tape. Then, the remaining gaskets are laid so that the thickness is consistent with the preform, and the sealing tape continues to be laid to ensure sealing.
[0086] Step 3: Connect the carbon nanotube film sensor in the test mold to the data collection device.
[0087] Specifically, the other end of the previously reserved copper wire is connected to a digital multimeter; and the digital multimeter is connected to a computer.
[0088] Step 4: Pour the test liquid into the test mold, record the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculate the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform.
[0089] The step 4 is to pour the test liquid into the test mold, record the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculate the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform, which specifically includes:
[0090] Step 4.1: Pour a test liquid into the test mold, and record the change of the resistance of the carbon nanotube film sensor over time through the data collection device; the test liquid can be commercially available soybean oil, corn syrup or silicone oil, or a resin solution, etc., and its viscosity is generally less than 0.3 Pa·s.
[0091] Figure 4 The overall assembly diagram of the permeability testing system provided by the embodiment of the present invention is shown in FIG. Figure 4, after the laid carbon nanotube film sensor is connected to the data collection device, the glue inlet pipe is connected to the glue injection port 1-3 of the upper cover plate 1, and the temperature of the test liquid at this time is tested with a thermometer, and the viscosity of the test liquid at this time is obtained according to its temperature-viscosity curve. The glue outlet is vacuumed (negative pressure), and the specific operation method is as follows: the vacuum pump is connected to the liquid collection bottle through the air pipe, and the liquid collection bottle is connected to the glue outlet 1-3 of the upper cover plate 1 through the air pipe, the valve of the glue injection port is closed, and the vacuum pump is turned on. When the pressure gauge reading is -0.1MPa, the next step is prepared. The data collection device is turned on to record the resistance change of the carbon nanotube film sensor, the glue injection port is opened, and the test liquid flows into the mold under the injection pressure to infiltrate the fiber preform. During the liquid injection process, the liquid injection start time is recorded, and the resistance information is continuously collected. The complete resistance change curve is collected, and the flow front of the test liquid is observed to flow through the fiber preform through the glass observation window. Continue to test for a period of time, turn off the vacuum pump, turn off the data collection device, end the test, and obtain the resistance change data of the carbon nanotube film sensor over time.
[0092] Step 4.2: According to the position of each carbon nanotube film sensor in the fiber layer and the position of each carbon nanotube film sensor relative to the injection surface of the fiber preform, calculate the distances l1, l2, l3, etc. of each carbon nanotube film sensor relative to the injection surface of the fiber preform from bottom to top. n .
[0093] Step 5: Draw the L according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform 2 -t curve.
[0094] In step 5, the L is plotted based on the change in resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform. 2 -t curve, including:
[0095] Step 5.1: drawing a resistance-time point line graph according to the change of the resistance of the carbon nanotube film sensor over time;
[0096] The data of the change in the resistance (R) of each carbon nanotube film sensor over time t collected by the data collection device is plotted into a resistance-time point-line graph, namely, an Rt point-line graph.
[0097] Step 5.2: Draw a resistance relative change rate percentage-time curve graph based on the resistance-time point line graph using drawing software such as Origin.
[0098] Figure 5 A schematic diagram of a resistance relative change rate percentage-time curve provided by an embodiment of the present invention, see Figure 5 The characteristics of the resistance relative change rate percentage-time curve include a stable baseline, a resistance mutation stage, and a stable platform. The mutation point where the sensor resistance changes from a stable baseline to a resistance mutation stage is taken as the arrival time of the flow front of the permeate liquid. The mutation point is defined as the point where the relative resistance change rate percentage of the three consecutive points after this point is greater than 0.5%.
[0099] Step 5.3: After drawing the resistance relative change rate percentage-time curve, determine the response time of the test liquid reaching each carbon nanotube film sensor according to the relative resistance change rate percentage mutation point of the resistance relative change rate percentage-time curve, which are s1, s2, s3…s n ; The mutation point is defined as the resistance change rate of three consecutive points after this point is greater than 0.5%;
[0100] Step 5.4: Determine the position and time corresponding to the test liquid flow front contacting the carbon nanotube film sensor: L1 = l1, t1 = s1; L2 = l2, t2 = s2; ...; L n = l n , t n =s n ;
[0101] Step 5.5: Based on the corresponding relationship between the position L of the flow front of the test liquid and the corresponding time t, the flow front position square-time curve inside the fiber preform is drawn by drawing software such as Origin, that is, L 2 -t curve.
[0102] Step 6: Place the fiber preform inside L 2 The slope of the -t curve is substituted into Darcy's law to calculate the unsaturated permeability inside the fiber preform.
[0103] In step 6, the fiber preform interior L 2 The slope of the -t curve is substituted into Darcy's law to calculate the unsaturated permeability inside the fiber preform, specifically including:
[0104] Step 6.1: Obtain the internal L of the fiber preform by linear fitting 2 -t slope λ of the curve;
[0105] Step 6.2: Calculate the unsaturated permeability of the fiber preform according to Darcy's law Where η is the viscosity of the test liquid; φ is the porosity of the fiber preform; ΔP is the injection pressure; λ is L 2 -tThe slope of the linear fit of the curve.
[0106] The present invention realizes the determination of the unsaturated permeability inside the fiber preform by designing a permeability test system, which is composed of a test mold, a carbon nanotube film sensor and a data collection device. The method of the present invention first places the carbon nanotube film sensor into the fiber preform to be tested with a prefabricated hole, and places it at a preset position in the test mold, then connects the carbon nanotube film sensor to the data collection device, perfuses the test liquid, records the change in the resistance of the carbon nanotube film sensor, and calculates the distance between different carbon nanotube film sensors, and then processes the obtained data and enters Darcy's law to calculate the unsaturated permeability inside the fiber preform. The permeability test method based on the carbon nanotube film sensor monitoring the flow front of the present invention is simple to operate, has strong applicability, can accurately determine the unsaturated permeability inside the fiber preform, and improves the accuracy of testing the unsaturated permeability inside the fiber preform, and has broad application prospects.
[0107] Based on the method provided by the present invention, the present invention also provides a permeability testing device for monitoring the flow front based on a carbon nanotube membrane sensor, comprising:
[0108] Permeability testing system; the permeability testing system comprises a testing mold, a carbon nanotube film sensor and a data collection device;
[0109] The sensor placement and mold assembly module is used to place the carbon nanotube film sensor into the fiber preform to be tested with the prefabricated hole, place it at a preset position in the test mold, and assemble the test mold;
[0110] A data collection device connection module, used to connect the carbon nanotube film sensor in the test mold to the data collection device;
[0111] A data collection and recording module, used for pouring a test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculating the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform;
[0112] A curve drawing module, used for drawing a flow front position square-time curve inside the fiber preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform;
[0113] The permeability calculation module is used to substitute the slope of the flow front position square-time curve inside the fiber preform into Darcy's law to calculate the unsaturated permeability inside the fiber preform.
[0114] The following provides three specific embodiments of a permeability test method for monitoring a flow front based on a carbon nanotube membrane sensor according to the present invention.
[0115] Embodiment 1:
[0116] The carbon fiber needle-punched preform was used as the test object, with a fiber volume fraction of 15%. The needle-punched preform was cut into 70×25×15mm, and a 3mm diameter hole was prefabricated every 10mm. A carbon nanotube film sensor was placed, and a total of 6 carbon nanotube film sensors were laid. The size of the carbon nanotube film used was 30mm×2mm×12μm (length×width×thickness), and the initial resistance was 15Ω. The glass fiber sleeve used was 35mm in length, 1mm in outer diameter, 0.1mm in wall thickness, and 0.017g / cm in linear density. Phenolic resin solution was used as the test liquid, the experimental temperature was 29℃, the corresponding viscosity was 0.099Pa·s, and the pressure of the vacuum pump was adjusted to 0.1MPa. The data of each carbon nanotube film sensor are: L1 = 10 mm, t1 = 6.24 s; L2 = 20 mm, t2 = 6.72 s; L3 = 30 mm, t3 = 7.44 s; L4 = 40 mm, t4 = 8.41 s; L5 = 50 mm, t5 = 9.80 s, L6 = 60 mm, t6 = 11.52 s. The slope of the linear fitting is λ = 6.67 × 10 -4 , substituting Darcy's law to obtain the internal unsaturated permeability K = 2.88 × 10 -10 m 2 Through simulation calculation, the influence of implanted carbon nanotube membrane sensor on resin flow rate is 7.02%. It can be considered that the influence is small and the permeability test result is accurate.
[0117] Embodiment 2:
[0118] use Glass fiber three-dimensional woven preform The fiber volume fraction is 50%. The needle punched preform is cut into 70×20×15mm, and a hole with a diameter of 3mm is prefabricated every 10mm. A carbon nanotube film sensor is placed, and a total of 6 carbon nanotube film sensors are laid. The size of the carbon nanotube film used is 30mm×2mm×10μm (length×width×thickness), and the initial resistance is 11Ω. The glass fiber sleeve used is 35mm long, 1mm in outer diameter, 0.1mm in wall thickness, and 0.017g / cm2 in linear density. Soybean oil is used as the test liquid, the experimental temperature is 25.5℃, the corresponding viscosity is 0.103Pa·s, and the pressure of the vacuum pump is adjusted to 0.1MPa. The data of each carbon nanotube film sensor are: L1 = 10 mm, t1 = 11.25 s; L2 = 20 mm, t2 = 13.80 s; L3 = 30 mm, t3 = 18.18 s; L4 = 40 mm, t4 = 24.09 s; L5 = 50 mm, t5 = 32.05 s, L6 = 60 mm, t6 = 40.25 s. The slope of the linear fitting is λ = 1.19 × 10 -4, substituting Darcy's law to obtain the internal unsaturated permeability K = 3.72 × 10 -11 m 2 Through simulation calculation, the influence of implanted carbon nanotube membrane sensor on resin flow rate is 6.52%. It can be considered that the influence is small and the permeability test result is accurate.
[0119] Embodiment 3:
[0120] Carbon fiber plain fabric laminate was used as the test object, with a fiber volume fraction of 55%. The fabric was cut into 70×23×15mm, and a 3mm diameter hole was prefabricated every 10mm. A carbon nanotube membrane sensor was placed, and a total of 6 carbon nanotube membrane sensors were laid. The size of the carbon nanotube membrane used was 40mm×2mm×12μm (length×width×thickness), and the initial resistance was 18Ω. The glass fiber sleeve used was 35mm long, 1mm in outer diameter, 0.15mm in wall thickness, and 0.015g / cm in linear density. Ethylene glycol was used as the test liquid, the experimental temperature was 18℃, the corresponding viscosity was 0.023Pa·s, and the pressure of the vacuum pump was adjusted to 0.1MPa. The data of each carbon nanotube film sensor are: L1 = 10 mm, t1 = 7.02 s; L2 = 20 mm, t2 = 7.35 s; L3 = 30 mm, t3 = 7.98 s; L4 = 40 mm, t4 = 8.51 s; L5 = 50 mm, t5 = 9.60 s, L6 = 60 mm, t6 = 11.02 s. The slope of the linear fitting is λ = 8.87 × 10 -4 , substituting Darcy's law to obtain the internal unsaturated permeability K = 8.36 × 10 -11 m 2 Through simulation calculation, the influence of implanting carbon nanotube membrane sensor on resin flow rate is 2.11%. It can be considered that the influence is small and the permeability test result is accurate.
[0121] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for testing the internal permeability of a fiber preform using a carbon nanotube film as a sensor, characterized in that: include: Prepare a permeability test system; the permeability test system includes a test mold, a carbon nanotube film sensor and a data collection device; Put the carbon nanotube film sensor into the fiber preform to be tested with the preformed hole, put it in the preset position in the test mold, and assemble the test mold; connecting the carbon nanotube film sensor in the test mold to the data collection device; Infusing the test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculating the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform; Draw a flow front position square-time curve inside the preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform; The slope of the flow front position square-time curve inside the fiber preform is substituted into Darcy's law to calculate the unsaturated permeability inside the fiber preform.
2. The method according to claim 1, characterized in that The prepared permeability test system specifically comprises: Prepare a test mold; the test mold includes an upper cover plate, a gasket, and a lower base plate; the upper cover plate is provided with injection / discharge ports at the center of the left and right sides, through holes are provided around it, and the center part of the upper cover plate is a glass observation window; the gasket has a thickness ranging from 10 to 50 mm, the middle part is hollowed out, and through holes are provided around it in the same structure as the upper cover plate; the lower base plate is a rectangular structure, and the edges have through holes in the same structure as the upper cover plate.
3. The method according to claim 2, characterized in that The prepared permeability test system further comprises: Cut out carbon nanotube film samples of preset specifications using a laser marking machine; Use sandpaper to polish the insulation layer at both ends of the copper wire; One end of the polished copper wire is bonded to the carbon nanotube film sample using conductive silver glue, and the other end is kept aside for compaction and solidification; The solidified carbon nanotube film is placed in a glass fiber sleeve with a loosened surface to prepare a carbon nanotube film sensor.
4. The method according to claim 2, characterized in that: The carbon nanotube film sensor is placed in the preformed fiber to be tested with the preformed hole, and placed in a preset position in the test mold, and the test mold is assembled, specifically including: Prefabricate holes at intervals on the preform to be tested; Put the prepared carbon nanotube film sensor into the hole of the preform to be tested; placing a preform of an assembled carbon nanotube film sensor on the lower base plate; Place the gasket on the lower base plate. The total thickness of the gasket should be the same as the height of the preform. While reserving the injection / discharge port position, lay a sealing tape with the same thickness as the gasket around the preform to be tested to ensure a vacuum environment. The upper cover plate is placed on the lower base plate, and bolts are used to lock and seal the upper cover plate, the gasket, and the lower base plate through the through holes around the upper cover plate, the gasket, and the lower base plate in sequence, and the test mold is assembled.
5. The method according to claim 4, characterized in that The at least 5 carbon nanotube film sensors are arranged in parallel in the length direction inside the preform, and the distance between two adjacent carbon nanotube film sensors is 1 cm or more. The thickness of the carbon tube film ranges from 10-15μm, and the resistance ranges from 10-30Ω. The fiber preform, the fiber types include carbon fiber, glass fiber, basalt fiber, aramid fiber, silicon carbide fiber, etc. The fiber preform, the preform types include fabric laminates, woven fabrics, braids, needle-punched preforms, stitched fabrics, etc. The glass fiber sleeve has a length of 30-50mm, an outer diameter range of 1-2mm, a wall thickness range of 0.1-0.2mm, and a linear density range of 0.01-0.03g / cm. The prefabricated hole diameter ranges from 2-4mm, and the spacing ranges from 5-20mm.
6. The method according to claim 1, characterized in that The step of connecting the carbon nanotube film sensor in the test mold to the data collection device specifically includes: The data collection device includes a digital multimeter and a computer; The other end of the reserved copper wire is fixed to the two ends of the carbon nanotube film sensor by using conductive silver glue, and the other end of the copper wire is connected to the digital multimeter; the digital multimeter is connected to the computer.
7. The method according to claim 1, characterized in that The step of pouring the test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time by the data collection device, and calculating the distances of different carbon nanotube film sensors relative to the injection surface of the fiber preform, specifically includes: Infusing the test liquid into the test mold, and recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device; According to the position of each carbon nanotube film sensor laid in the fiber layer and the position of each carbon nanotube film sensor relative to the injection surface of the fiber preform, the distances l1, l2, l3, etc. of each carbon nanotube film sensor relative to the injection surface of the fiber preform are calculated from bottom to top. n .
8. The method according to claim 7, characterized in that The method of drawing a flow front position square-time curve inside the fiber preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform specifically includes: Draw a resistance-time point line graph according to the change of the resistance of the carbon nanotube film sensor over time; Draw a resistance relative change rate percentage-time curve graph according to the resistance-time point line graph; The response time s1, s2, s3, s... of the test liquid reaching each carbon nanotube film sensor is determined according to the resistance change rate mutation point of the resistance relative change rate-time curve. n ; The mutation point is defined as the resistance change rate of three consecutive points after the mutation point is greater than 0.5%; Determine the position and time corresponding to the contact of the test liquid flow front with the carbon nanotube film sensor as follows: L1 = l1, t1 = s1; L2 = l2, t2 = s2; ...; L n = l n , t n =s n ; A flow front position square-time curve inside the fiber preform is plotted based on the corresponding relationship between the position L of the test liquid flow front and time t.
9. A permeability test device for monitoring flow front based on carbon nanotube membrane sensor, characterized in that: include: Permeability testing system; the permeability testing system comprises a testing mold, a carbon nanotube film sensor and a data collection device; A sensor placement and mold assembly module is used to place the carbon nanotube film sensor into the fiber preform to be tested with a prefabricated hole, place it at a preset position in the test mold, and assemble the test mold; A data collection device connection module, used to connect the carbon nanotube film sensor in the test mold to the data collection device; A data collection and recording module, used for pouring a test liquid into the test mold, recording the change of the resistance of the carbon nanotube film sensor over time through the data collection device and calculating the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform; A curve drawing module, used for drawing a flow front position square-time curve inside the fiber preform according to the change of the resistance of the carbon nanotube film sensor over time and the distance of different carbon nanotube film sensors relative to the injection surface of the fiber preform; The permeability calculation module is used to substitute the slope of the flow front position square-time curve inside the fiber preform into Darcy's law to calculate the unsaturated permeability inside the fiber preform.
